Using Coupled Rheometer-FBRM to Study Rheological Properties and Microstructure of Cemented Paste Backfill - Hongjiang Wang; Liuhua Yang; Hong Li; Xu Zhou; Xiaotian Wang (Advances in Materials Science and Engineering)
Rheological properties, such as the yield stress, viscosity, and thixotropy, are related to the microstructure of cemented paste backfill (CPB). To highlight the relationship, two instruments were combined to measure the changes in the microstructure and the rheological properties of CPB simultaneously. In this way, the particle/agglomerate size distribution characterized by the focused beam reflectance measurement (FBRM) and the rheological factors measured by the rheometers could be directly linked. The results show that when under shearing, the intrinsic network structure of CPB responds to the shear-induced stresses with the interference of interparticle forces, leading to changes in the rheological behavior. Shear thinning can be found in CPB suspensions with a microstructure that is either loose interconnection or random. With an increase in the shear rate, random collisions among particles become organized in the flow, lowering the yield stress and viscosity. However, when the shear rate exceeds a certain threshold value, the rheological parameters change as a result of shear thickening. The results of this study contribute to better understanding of the complex rheological behavior of CPB.